Quality control of bedside DR in neonatal chest radiography using a chest stabilization device and its clinical application - Xinqi Zhang; Yinfeng Zhang (BMC, 2020)
Abstract Background To develop a method for movement control during radiation exposure and to improve image quality of bedside thoracic DR in neonates. Methods Total 60 cases of neonates' thoracic DR X-ray images, which were taken before and after neonates' movement control, were compared and analyzed. X-ray exposure was set at 47 kV/1.4 mAs for all films that were taken without movement control, while various exposure conditions were used based on the neonate's body weight when the neonate's movement was controlled. Results The radiation dose of X-ray exposure was significantly lower after neonates' movement control (7.32 ± 0.20 μGy) than that before the movement control (24.20 ± 0.82 μGy, P <  0.05), and it was decreased most dramatically in the neonates with lowest body weight (70%). After neonates' movement control, image quality was significantly improved (44 cases out of 60, 73.3%) compared to that before movement control (only 5 out 60, 8.3%, P <  0.05). There was no significant difference in the score of image background noise before and after movement control (P <  0.05). Conclusion Movement control with simple device could not only significantly improve the image quality, but also remarkably reduce radiation exposure dose.